The consequences of changes in forest land cover in the Alpine and Jurassic massifs on the physico-chemical status of deep lake waters - Van Tuan Nghiem; Rachid Nedjai; Nacer Nasreddine Messaoud (Revue de Géographie Alpine)
The issue of acidification in lake waters has been the topic of numerous scientific studies in northern Europe and North America. In recent years, interest in the topic has spread to southern Europe and Asia because similar symptoms have been observed (drop in pH and in redox potential, generally accompanied by oxygen depletion). All the scientific work on the issue has concluded that the phenomenon is general and affects, to different degrees, lakes located at low to medium altitudes in mountains (the Vosges mountains and more recently the Jura mountains, in France). The difference in degree is often interpreted as the result of different combinations from three sources, namely acid rain, direct discharges of pollutants and the spread of forests (essentially conifer species). The first two sources have been confirmed, but the third is less perceptible due to slow progression of the phenomenon.Analysis and modelling of changes in land cover in the Hérisson river basin in the Jura mountains (largely carbonated soils) confirmed the direct impact of the forest cover on the physico-chemical quality of lake waters, in particular at the deeper levels (hypolimnion) over the past 30 years. The impact is reinforced by the considerable presence of peat zones around the lakes which, during high-water periods, contribute large quantities of dissolved, particulate organic matter.The goal of this work is to show the direct impact of the increasing forest cover observed on the Jurassic plateaus, caused by a considerable reduction in farming activity over the past 30 years. This work focuses on an analysis of land cover (vegetation), using four satellite images spanning the period from 1975 to 2006, and calls on hydrogeochemical modelling (WARMF) to evaluate changes in the physico-chemical quality, i.e. acidification, of deep lake waters. This first step is followed by a predictive phase prior to measuring the intensity of the physico-chemical changes (pH and redox) over the next 20 years to 2030. The existence of this phenomenon confirms the massive releases of heavy metals recently noted and the biological weakening observed in certain lakes, notably among the benthic fauna.